Adoption and diffusion of renewable energy technologies: Influence of the policy mix in the manufacturing industry - Katharina Mattes; Simon Müller; Angela Jäger; Nadezda Weidner; Ute Weißfloch (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
Rising energy prices and political goals which address climate change, such as the reduction of greenhouse gas emissions, increase the importance of using renewable energies and technologies for generating these. Since the manufac-turing industry is one of the major energy consumers in Germany, this paper focuses on the diffusion of renewable energy technologies to generate power in the manufacturing industry. Using data from the German Manufacturing Survey 2012 for 1,594 firms, we analyse the relation between the usage of renewable energy technology and firms' characteristics, also accounting for structural de-terminants. In addition, the reasons for the decision to use these technologies and, in particular, the relevance of the political framework are examined. Our findings show that the producers of end-consumer goods are more likely to use renewable energy technologies compared to other manufacturing firms. The availability of resources plays a substantial role, whereas the energy intensity of the firm is less important for the introduction of renewable energy technologies. When considering the chosen reasons for adoption, firms mentioned most fre-quently that they anticipate rising energy prices. The policy mix, however, is less often mentioned and mostly together with other reasons.
urn:nbn:de:0011-n-2942282
Keywords: 330; renewable energy technologies; manufacturing industry; technology adoption; diffusion of innovations; quantitative analysis